Cost-effectiveness of emergency preparedness measures in response to infectious respiratory disease outbreaks: a systematic review and econometric analysis. Issue 4 (29th April 2021) - Vardavas, Constantine; Nikitara, Katerina; Zisis, Konstantinos; Athanasakis, Konstantinos; Phalkey, Revati; Leonardi-Bee, Jo; Johnson, Helen; Tsolova, Svetla; Ciotti, Massimo; Suk, Jonathan E
Abstract : Objectives: Respiratory infectious disease outbreaks pose a threat for loss of life, economic instability and social disruption. We conducted a systematic review of published econometric analyses to assess the direct and indirect costs of infectious respiratory disease outbreaks that occurred between 2003 and 2019. Setting: Respiratory infectious disease outbreaks or public health preparedness measures or interventions responding to respiratory outbreaks in OECD countries (excluding South Korea and Japan) so as to assess studies relevant to the European context. The cost-effectiveness of interventions was assessed through a dominance ranking matrix approach. All cost data were adjusted to the 2017 Euro, with interventions compared with the null. We included data from 17 econometric studies. Primary and secondary outcome measures: Direct and indirect costs for disease and preparedness and/or response or cost-benefit and cost-utility were measured. Results: Overall, the economic burden of infectious respiratory disease outbreaks was found to be significant to healthcare systems and society. Indirect costs were greater than direct costs mainly due to losses of productivity. With regard to non-pharmaceutical strategies, prehospitalisation screening and the use of protective masks were identified as both an effective strategy and cost-saving. Community contact reduction was effective but had ambiguous results for cost saving. School closure was an effective measure, but not cost-saving in the long term. Targeted antiviral prophylaxis was the most cost-saving and effective pharmaceutical intervention. Conclusions: Our cost analysis results provide evidence to policymakers on the cost-effectiveness of pharmaceutical and non-pharmaceutical intervention strategies which may be applied to mitigate or respond to infectious respiratory disease outbreaks.